Influence of Entrepreneurship Orientation on Business Performance of Broiler Husbandry in The Partnership and The Independent Scheme in Bogor - Idham Haliq; Rachmat Pambudy; Burhanuddin Burhanuddin; Syafik Alfikri (International Journal of Agriculture System, 2018)
The purpose of this research are: (1) to analyze the dimensions that construct the entrepreneurship orientation of broiler husbandry entrepreneur in partnership and independent scheme, (2) to analyze the influence of entrepreneurship orientation on business performance of broiler husbandry in the partnership and the independent scheme. This research was conducted in March-May 2017, employed 30 respondent farmers on each partnership and independent scheme. Structural-Partial Least Square Equation Modeling (SEM-PLS) was employed for quantitative analysis. The results of this study indicated that the dimension of entrepreneurship that can be observed from the business actors of broiler husbandry in the independent scheme at the Bogor Regency was innovative, proactive, risk- taking, autonomy and competitive aggressiveness. While in the partnership scheme there was no observable orientation dimension. The partnership scheme showed a negative and insignificant influence of entrepreneurship orientation to business performance, whereas the independent scheme showed a positive and significant influence of the entrepreneurship orientation to the business performance.